Neighborhood social capital, juvenile delinquency, and victimization: results from the international self-report delinquency study - 3 in 23 countries - Binik, Oriana (European journal on criminal policy and research, 2019)
Since the beginning of the twentieth century, criminology has attempted to identify ecological factors affecting the rise or the decrease in crime rates. In this framework, concepts of “social disorganization”, “collective efficacy”, and “social capital” have been coined. Particularly in recent years, the perspective of “social capital” has attracted the interest of criminologists, but, despite the numerous studies conducted in this field, some issues remain open. Firstly, studies conducted outside the US context are few. Secondly, even in North American studies, there is a disagreement over the impact of social capital on crime, in particular on violent crimes. The results of this study, conducted on data obtained by the ISRD3 survey in 23 countries around the world, and addressed to 7th, 8th, and 9th grade students (N = 55,201), try to address such issue: they show a negative correlation between social capital and self-reported crime also outside North America, both for violent crimes and general delinquency. The preventive role played by social capital on crime is also confirmed considering the self-reported data on victimization.